Teaching Labor Laws: Evidence From a Randomized Control Trial in South Africa - Marianne Bertrand; Bruno Crépon (Institute of Labor Economics (IZA), 2020)
We assess whether imperfect knowledge of labor regulation hinders job creation at small and medium-sized firms. We partner with a labor law expert that provides information about labor regulation via newsletters and access to a specialized website. We randomly assign 1800 firms to get access to this service for a 21-week period. Six months later, the average employment level at treatment firms was 12% higher than at control firms. The intervention decreased the perception that labor regulation is a constraint to hiring and increased optimal employment level.
Keywords: J23; J63; J64; J68; 330; labor demand; labor laws